Offences, Punishment and Rehabilitation in the Vinaya Pitaka - Acharya, Deepak Prasad (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: The Vinaya Pitaka, a comprehensive Buddhist scripture, contains a rich repository of ethical and moral guidelines. Objective: This research paper explores the descriptions of criminal and other offences within the Vinaya Pitaka and the associated penalties. This paper explores the significance of discipline and ethical conduct in the Vinaya Pitaka, analyzing the categorization of offences, the purpose of punishments, and the emphasis on rehabilitation. The study also aims to shed light on the socio-ethical aspects of the Vinaya Pitaka and its potential relevance in contemporary ethical discourse. Methodology: Library based textual analysis of the Vinaya Pitaka, focusing on the division of offences and their respective punishments within the Buddhist monastic context has been applied to carryout this research. Result: Through the detailed study, it has been found that the detailed account of offences and punishments provides valuable insights into the Saṅgha's emphasis on maintaining order, harmony, and adherence to the Buddha's teachings. Through a systematic analysis of the text, this paper provides insights into the understanding of criminal behaviour and sanctions within the Buddhist monastic context. The Pātimokkha, a crucial text within the Vinaya Pitaka, outlines the code of conduct for Buddhist monks and nuns. Its detailed system of offences and punishments reflects a unique approach to monastic discipline, emphasizing rehabilitation and restoring harmony within the monastic community. Conclusion: This paper examines the purpose of punishments in the Pātimokkha, highlighting its restorative nature and its alignment with Buddhist principles of compassion and non-violence.